(untitled) (Bangladesh Medical Journal, 2014)
Multi-drug resistant tuberculosis (MDR-TB) is a form of TB resistant to isoniazid and rifampicin and considered as a major threat to TB control worldwide. Limited data are available regarding risk factors and serum zinc status of MDR-TB in Bangladesh. Tuberculosis is a disease which blocks a key part of the bodys immune defense. As zinc deficiency causes immune suppression, we assume that it may play a role in the development of MDR-TB. So, this study was carried out to evaluate and assess the serum zinc level as well as different risk factors in patients of MDR-TB. This case control study was carried out in the Department of Clinical Pathology, in collaboration with Department of Public Health and Informatics, Department of Biochemistry, BSMMU and National tuberculosis referral laboratory (NTRL) in NIDCH, Mohakhali, Dhaka from March 2012 to February 2013.We enrolled 50 newly diagnosed cases of MDR-TB patients from NTRL and 50 age matched healthycontrols from a selective community Sirajdikhan Upazilla, Munshiganj District. The two groups were compared based on various demographic factors, behavioral factors, factors related with personal illness history and also laboratory related factors. Serum zinc deficiency, changing trend of number of family members, presence of smoking history, absence of BCG scar and past history of contact TB were statistically significant risk factors for development of MDR-TB in logistic regression model. In our study, we found the mean (SD) serum zinc level in case group 60.40 (8.91) ?g/dL and 84.00 (13.62) ?g/dL in healthy controls which was significant statistically. The risk factors that we found, specially lower level of serum zinc, are the major concern for the development of MDR-TB and attempt to minimize them might contribute to control TB DOI: http://dx.doi.org/10.3329/bmj.v43i1.21368 Bangladesh Med J. 2014 January; 43 (1): 3-8